2012
DOI: 10.1556/avet.2012.035
|View full text |Cite
|
Sign up to set email alerts
|

Study of the genetic variability of porcine circovirus type 2 detected in Serbia and Slovenia

Abstract: Recent variants of porcine circovirus type 2 (PCV2) were obtained from tissues of domestic pigs with porcine circovirus associated disease and from randomly selected wild boar samples from Serbia and Slovenia. A 450-base-pair nucleotide sequence was obtained by PCR from the ORF2. The derived nucleotide and amino acid sequences were aligned and compared to the corresponding region of closely related PCV2 sequences determined in previous years and retrieved from the GenBank. The 30 Serbian and 17 Slovenian PCV2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…These latter analyses were carried out using the complete PCV2 genome, the complete ORF1, a partial ORF1 sequence, the complete ORF2 and a partial ORF2 sequence. Partial ORF1 and ORF2 analyses were performed since only partial ORF1 and ORF2 sequences were recovered from previous Croatian and neighbour countries (Slovenia and Serbia) sequences (Toplak and others 2012). …”
Section: Methodsmentioning
confidence: 99%
“…These latter analyses were carried out using the complete PCV2 genome, the complete ORF1, a partial ORF1 sequence, the complete ORF2 and a partial ORF2 sequence. Partial ORF1 and ORF2 analyses were performed since only partial ORF1 and ORF2 sequences were recovered from previous Croatian and neighbour countries (Slovenia and Serbia) sequences (Toplak and others 2012). …”
Section: Methodsmentioning
confidence: 99%
“…In the neighbouring country Serbia besides immunohistochemistry, PCR was successfully used for the detection and later on for molecular characterization of circulating PCV2 strains [8,9]. Ogawa et al [13] examined 33 principal organs collected from PRDC/PMWS-suspected pigs and 26 organs of aborted foetuses by multiplex PCR for the presence of PCV2 and PPV.…”
Section: Discussionmentioning
confidence: 99%
“…The standard laboratory methods for diagnosis of diseases caused by PCV2 are mainly based on immunohistochemistry and in situ hybridization directly in tissue samples or by real-time quantitative polymerase chain reaction [5,6]. Also the conventional polymerase chain reaction is often used as a standard method for detection of PCV2 in clinical samples [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Serbia, the PCV2 related attention has been focused on the problem of growing pigs, but not on sows in service, even though PCV2 infection can be transmitted by semen (Schmoll et al, 2008). Study of 30 Serbian PCV2 sequences indicated that the predominant genotype in Serbia is PCV2b which is closely related to those previously described in Europe (Toplak et al, 2012;Savić et al, 2012). Vaccination against PCV2 is not obligatory and is being implemented mainly after the occurrence of clear clinical features of the disease.…”
Section: Introductionmentioning
confidence: 91%